DEVELOPMENT OF THE DECISION SUPPORT SYSTEM METHOD TO ANALYZE THE ISO 9001 QUALITY ASSURANCE SYSTEM AND ISO 45001 AND ISO 14001 SAFETY SYSTEMS - Pamungkas, Giantoro; Apriani, Ani; Dewi, Mina Wati (Universitas Bina Bangsa, 2024)
To what extent do the implementations of ISO 9001, ISO 45001, and ISO 14001 improve the bottom lines of manufacturing companies? that was the topic that motivated this study's research team. Incorporating data processing tools, this study technique is quantitative in nature. A digital questionnaire sent through the internet in a